Global Research Trends on the Role of Chlorogenic Acid on Antidiabetic Mechanisms and Reproductive Hormone Regulation (2015-2025): A Bibliometric Analysis - Eko Naning Sofyanita; Ari Suwondo; Heri Nugroho; Achmad Zulfa Juniarto (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Chlorogenic acid (CGA) is a natural chemical discovered in a variety of plants that has been associated with numerous health benefits. Recent evidence suggests that CGA impacts reproductive hormone regulation, thus linking metabolic health and endocrine function. Understanding trends and gaps in research at this intersection is crucial. This study characterizes global research patterns, collaboration, and thematic evolution on CGA's antidiabetic activity and its influence on reproductive hormones through bibliometric analysis. Methods: Data were retrieved from the Scopus database using the keywords (